Why don't things fall up? - Bentley, Dawn; Milne, A. A. (Alan Alexander), 1882-1956; Devaney, Adam ([Maitland, Fla.] : Advance Publishers, 2005)
"Pooh discovers gravity"--cover [p. 4].
Based on the "Winnie the Pooh" works, by A. A. Milne and E. H. Shepard.
Keywords: Gravity -- Juvenile literature